Preparation and Optical Characterization of Polymer Composites Reinforced by Natural Materials. - Jasim, Aseel S (Al-Nahrain Journal of Science, 2018)
Three groups of composite materials were prepared by using casting method from Unsaturated Polyester with volume fraction (70%) reinforced by Rice Husks with volume fraction (30%) (first group), the second group was prepared from Unsaturated Polyester with volume fraction (70%) reinforced by Rice Husks with volume fraction (15%) and by Palm Fibers with volume fraction (15%) (hybird composite) and the third group consist also of Unsaturated Polyester with volume fraction (70%) reinforced by Palm Fibers with volume fraction (30%), the length of palm fibers was (2-3) mm. Parameters such as absorbance (A), transmittance (T), reflectance(R), refractive index (n), extinction coefficient (k) , real (εr) and imaginary parts (εi) of dielectric constants, were studied in the spectral range (200-800) nm. The results show that the absorbance increases with increasing the ratio of Palm Fibers while the transmittance decreases, the hybrid composite has the best values of reflectance and the higher values of extinction coefficient, Refractive index, real and imaginary parts of dielectric constants were for samples containing ratios of Palm Fibers and the lower values were for those contain Rice Husks only.